2002
DOI: 10.1038/sj.onc.1205452
|View full text |Cite
|
Sign up to set email alerts
|

BCR/ABL P190 transgenic mice develop leukemia in the absence of Crkl

Abstract: The Bcr/Abl fusion protein directly causes chronic myelogenous leukemia and Philadelphia-chromosome positive acute lymphoblastic leukemia. Multiple independent studies have implicated Crkl, a small adapter protein, in transduction of oncogenic signals of Bcr/Abl and Crkl tyrosine-phosphorylation is used as a diagnostic tool for Philadelphia-positive leukemia. To evaluate the contribution of Crkl to this type of leukemia, we generated mutant mice that lack Crkl expression. We found that the overall survival of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…The authors of this paper did not examine the levels of CrkL (Imaizumi et al, 1999). Furthermore, in CrkL knockout study, it is described that the expression level of CrkII was not altered in the mice lacking CrkL (Hemmeryckx et al, 2002). In fact, we have established CrkII knockdown cells by using three human sarcoma cell lines and a glioblastoma cell line, and we did not observe the increase of the levels of CrkL in these cell lines (data not shown).…”
Section: Discussionmentioning
confidence: 72%
“…The authors of this paper did not examine the levels of CrkL (Imaizumi et al, 1999). Furthermore, in CrkL knockout study, it is described that the expression level of CrkII was not altered in the mice lacking CrkL (Hemmeryckx et al, 2002). In fact, we have established CrkII knockdown cells by using three human sarcoma cell lines and a glioblastoma cell line, and we did not observe the increase of the levels of CrkL in these cell lines (data not shown).…”
Section: Discussionmentioning
confidence: 72%
“…However, a recent study demonstrated that CML can still develop in CrkLknockout mice when bred to BCR-ABL P190-transgenic mice [52]. Although the lack of phenotype may be explained by mouse strain-specific effects or functional compensation by other related proteins, these results do suggest that CrkL is not absolutely required for leukemogenesis in vivo.…”
Section: Discussionmentioning
confidence: 93%
“…The inhibition of complexes mediated by the CRKLSH3(1) domain in CML cell lines and primary isolates from patient cells can inhibit the proliferation of these cells . By contrast, enhanced expression of CRKL has just the opposite e ect: mice transgenic for the p190 Bcr ± Abl protein developed leukaemia more rapidly when CRKL was overexpressed four-to sixfold (Hemmeryckx et al, 2001). …”
Section: Human Leukaemic Abl Kinasesmentioning
confidence: 99%